Jack and Jekyll La dégénérescence en Grande-Bretagne, 1880-1914 - Saudo-Welby, Nathalie (Signes, 2023)
At the end of the nineteenth century, Europe was haunted by a fear of decline that was sometimes formulated in terms of degeneration. In Great-Britain some thinkers and scientists warned against "racial decline", morbid heredity and social pathology. By exploring this context, also marked by the revival of Gothic fiction, this book brings into view a few lesser-known works novels and throws light on popular works of fiction, such as Strange Case of Dr Jekyll and Mr Hyde, The Picture of Dorian Gray, The Island of Doctor Moreau, Dracula and the adventures of Sherlock Holmes. Degenerating creatures go back through their personal, family and biological history. Their bodies are uncanny yet recognizable, monstrous yet readable. Some novelists spoke in favour of regeneration, others blurred the boundaries between morbidity and powerfulness, the patient and the doctor, the degenerate and the social reformer, the moral madman and the moral maniac. In creating characters that were so unfit that they must finally die, late-Victorian writers turned degeneration into a creative act.